Analisis Kompetensi Sumber Daya Manusia Dan Penerapan Akuntabilitas Terhadap Pengelolaan Keuangan Dana Desa di Desa Kolilanang Kecamatan Adonara Kabupaten Flores Timur - Agnes Derang Duli; Anthon Simon Y. Kerihi; Novi Theresia Kiak (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine Human Resources (HR) Competency and the application of accountability to financial management of village funds seen from human resource competence and financial management stages starting from planning, implementation, administration, reporting and accountability. This research is descriptive qualitative in nature with the data collection technique in the research being triangulation with the data analysis method used in this research being the Miles and Huberman model. Based on the research results, it can be seen that: (1) Competency of Human Resources in financial management of village funds is not yet optimal and effective, this can be seen from the level of education of village officials which is still low so that understanding of financial management of village funds is not carried out effectively. (2) The implementation of accountability in the management of village funds in Kolilanang Village from the planning stage to the accountability stage is said to be not yet accountable, because at the implementation stage there is still excess budget remaining so that the assessment of government performance is not yet effective and optimal. For several other stages, they are accountable.